ORGANIZATIONAL AND TECHNICAL MEASURES TO CREATE CONDITIONS FOR IMPLEMENTING THE METHOD FOR EVALUATING THE EFFICIENCY OF MANAGEMENT DECISIONS - Ulyana V. Maltseva (Вестник Северо-Кавказского федерального университета)
Given the competitive world, there is always a need for a distinctive feature to move ahead and overtake the competitors. Establishing an anti-crisis unit will not develop this feature, yet will create all the conditions for efficient management at the enterprise, not only in times of crisis, but constantly. The consumer preferences change just like the distinctive features do; an anti-crisis unit will enable the company to respond adequately to the changes, which will have a positive effect on the stability on the market.